Incompetent lip seal affects the form of facial soft tissue in preschool children. Issue 5 (3rd September 2021) - Inada, Emi; Saitoh, Issei; Kaihara, Yasutaka; Murakami, Daisuke; Nogami, Yukiko; Kubota, Naoko; Shirazawa, Yoshito; Ishitani, Norihito; Oku, Takeshi; Yamasaki, Youichi
ABSTRACT: Objective : To examine whether incompetent lip seal (ILS) influences the form of facial soft tissue. Methods : Four hundred forty-four preschool children 3–5 years of age were selected. The images of the subjects' facial surface were obtained with a three-dimensional laser scanner. Coordinates of 16 facial landmarks were established and identified on the three-dimensional facial images, and the differences between children with (wILS) and without ILS (woILS) were measured. Results : The angle of sagittal facial convexity, excluding the nose, in 4- and 5-year-old children was significantly smaller in wILS children than in woILS children. The nasal prominence angle and the protrusion angle of lips in wILS children were significantly smaller than those in woILS children, at all ages. Conclusion : Children with ILS have anteriorly prominent subnasales and lips and flatter noses. The influence of ILS on facial form begins to appear even before 3 years of age.